IMPLEMENTASI KEBIJAKAN HUKUM PERDAGANGAN DI INDONESIA PADA SAAT TERJADINYA KOMPETISI DAGANG AMERIKA DENGAN CHINA [IMPLEMENTATION OF TRADE LAW POLICY IN INDONESIA AT THE TIME OF THE OCCURRENCE OF TRADE COMPETITION BETWEEN AMERICA AND CHINA] - Hadawang, M. Rusdyanto (Lex Prospicit, 2023)
This research examines the policies issued by the Government of Indonesia, especially in trade law policies at the time of trade wars or trade competition between America and China. This study uses a type of normative research through a legal history approach, a conceptual approach, an approach to legal principles, and a legal political approach in order to achieve the research objectives, namely to present legal facts and examine the impact of trade competition between America and China on Indonesia in the field of trade law at the time of the occurrence of trade competition between America and China with conformity to the principles stipulated in Article 2 of Law Number 7 of 2014 concerning Trade. The results of the study show that the impact that is felt by Indonesia is illustrated in the presentation of data on Indonesia's fluctuating export-import activities and also exposure regarding regulations and policies resulting from negotiations between countries as stipulated in international trade agreements that have been ratified and applied to the people of Indonesia. The resulting conclusion is that due to trade competition between America and China, Indonesia has issued regulatory changes related to export-import activities and also provisions in the defense industry which regulate the involvement of the private sector in the manufacture of defense equipment, through changes in Law Number 11 of 2020 concerning Job Creation and Law Number 16 of 2012 concerning the Defense Industry. Bahasa Indonesia Abstrak: Penelitian ini mengkaji tentang kebijakan yang dikeluarkan oleh Pemerintah Indonesia khususnya dalam kebijakan hukum perdagangan pada saat terjadinya perang dagang atau kompetisi dagang antara Amerika dengan China. Penelitian ini menggunakan jenis penelitian normatif melalui pendekatan sejarah hukum, pendekatan konseptual, pendekatan asas-asas hukum, serta pendekatan politik hukum guna mencapai tujuan penelitian yaitu untuk menyajikan fakta hukum dan mengkaji dampak kompetisi dagang antara Amerika dengan China terhadap Indonesia di bidang hukum perdagangan pada saat terjadinya kompetisi dagang antara Amerika dengan China dengan kesesuaian asas-asas yang diatur dalam Pasal 2 Undang-Undang Nomor 7 Tahun 2014 tentang Perdagangan. Hasil penelitian menunjukan bahwa dampak yang dirasakan Indonesia, tergambarkan dalam sajian data tentang kegiatan ekspor impor Indonesia yang fluktuatif dan juga pemaparan terkait regulasi dan kebijakan hasil perundingan antar negara yang dituang dalam perjanjian perdagangan internasional yang telah diratifikasi dan diberlakukan kepada masyarakat Indonesia. Kesimpulan yang dihasilkan bahwa dampak kompetisi dagang antara Amerika dengan China, Indonesia telah mengeluarkan perubahan regulasi terkait dengan kegiatan ekspor impor dan juga ketentuan dalam industri pertahanan yang mengatur keterlibatan pihak swasta dalam pembuatan alutsista, melalui perubahan dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dan Undang-Undang Nomor 16 Tahun 2012 tentang Industri Pertahanan.